2015
DOI: 10.17843/rpmesp.2015.321.1577
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de seguridad alimentaria y nutricional en familias del distrito de Los Morochucos en Ayacucho, Perú

Abstract: Objetivos. Evaluar la seguridad alimentaria y nutricional en familias del distrito Los Morochucos en Ayacucho, Perú. Materiales y métodos. Estudio basado en interpretación de la información disponible de fuentes oficiales y de encuestas realizadas para levantar la información no registrada en ellas. El muestreo fue estratificado y bietapico considerando 128 familias con al menos un niño menor de 12 años. Las variables fueron el nivel de seguridad alimentaria, percepción familiar sobre su situación de disponibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…In addition, the results of AEM and NTM are lower than the values found by Pillaca & Villanueva (2015); in the district of Los Morochucos (Ayacucho), where it was obtained that 96.4% of mothers practiced EB up to 6 months. The explanation of this percentage difference would be related to geo-social factors, considering the fact that mothers in AEM and NTM (coastal area) could not always comply with the practice of breastfeeding, because their children stay at home while they work, which is opposite to the context of the study cited in Ayacucho (mountain area), where mothers take their children with them (on their backs) during their daily work.…”
Section: Food Consumptionmentioning
confidence: 60%
“…In addition, the results of AEM and NTM are lower than the values found by Pillaca & Villanueva (2015); in the district of Los Morochucos (Ayacucho), where it was obtained that 96.4% of mothers practiced EB up to 6 months. The explanation of this percentage difference would be related to geo-social factors, considering the fact that mothers in AEM and NTM (coastal area) could not always comply with the practice of breastfeeding, because their children stay at home while they work, which is opposite to the context of the study cited in Ayacucho (mountain area), where mothers take their children with them (on their backs) during their daily work.…”
Section: Food Consumptionmentioning
confidence: 60%
“…Food insecurity studies Latin America largely focus on examining frequency, risk factors and outcome data [ 21 , 23 , 24 , 26 , 28 , 31 , 50 , 53 – 57 ], with few qualitative studies examining subjective experiences [ 15 , 20 , 21 ]. In this study, low income mothers of small children shared passages of their daily life shaped by the need to manage scarce resources.…”
Section: Discussionmentioning
confidence: 99%
“…Another stressor in our study was water insecurity, defined as having restrictions in the access to clean water that is estimated to affect more than 600 million people in the world [ 63 ]. A study showed that in a community of Ayacucho, Perú, 39% of households had food insecurity and none had access to safe drinking water [ 28 ]. Kirkpatrick and Tarasov [ 64 ] reported that low income families give up basic household services to purchase food.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important factor affecting biological use is hand washing. Pillaca and Villanueva () did find in the district Los Morocuchos (Ayacucho, mountain area, southern Peru) that only 74.2% of mothers washed their hands before preparing food, 48.4% before eating, 41.4% before feeding their children and 37.5% after going to the toilet. The percentage of families who always washed their hands with water and soap was 7.8%, which is an important factor to consider in future preventive strategies for intestinal‐infectious diseases.…”
Section: Introductionmentioning
confidence: 99%